PENGUKURAN EFEKTIVITAS PEMASARAN TAGLINE IKLAN SHOPEE DALAM MELIHAT MINAT KONSUMEN - Arafah, santu (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2019)
The tagline of the ad is a powerful marketing tool to motivate customers support a brand. The tagline of the ad utilized to make the buyer always remember with catchprasenya products. The tagline can create new image against a brandnya and persuasive effect to the community. In this case the ad tagline shopee that reads "buy all shopee, Free Ongkir" is an invitation to the public to buy any product to application shopee. This is the one who makes the effectiveness of advertising is very important to scrutinized, because advertising is a means to convey a message to the audience. This research method using a Customer Response Index (CRI) in looking at the effectiveness of Ad Shopee. Method of CRI includes awareness (awareness), comprehend (understanding), interest (interest), intention (intention), and action (action). The result of this analysis is that the ads effectiveness performance Shopee tagline used has exceeded 50% or exceed the average of the expectations of the consumer.